An experimental assessment of nonlinear effects of vertical motions of Naples systematic series planing hulls in regular waves. (June 2021) - Pigazzini, R.; De Luca, F.; Pensa, C.
Highlights: Detailed data analysis of regular waves motion responses, providing also a benchmark for computational studies. Assessment of nonlinear effects on vertical motions and accelerations. Nonlinear behavior characterized in the frequency domain: – First and second harmonic trends of vertical motions. – First three harmonic amplitudes trends of accelerations. Effects of wave steepness, slenderness ratio and speed on motion and acceleration harmonic content. First harmonic phase difference between wave and hull motions. Abstract: A comprehensive experimental assessment of vertical motions and accelerations of two Naples warped hard chine hulls systematic series (NSS) hulls in regular waves is presented. The seakeeping performance in regular waves are investigated, in particular nonlinear motion responses in terms of transfer functions and higher harmonic response as a function of wave frequency, steepness, hull slenderness and speed. In order to highlight the effects of wave properties on motion responses, transfer functions of both motion harmonics and phases are presented via iso-frequency and iso-steepness plots. Slenderness ratio is found to have a notable effect on motion transfer functions only at higher speeds. The presence of a higher harmonics in motion and acceleration response is also observed and the proposed analysis shows that increasing wave steepness and speed lead to increased higher harmonics responses of both vertical motions and accelerations. The effect of slenderness ratio on the second harmonic response of heave and pitch is only noticeable at higher speed. Phase difference between wave and motions shows that higher second harmonic content is generally associated with a higher phase lead. The main novelty of the present work is represented by the extensive analysis of NSS planing hulls in regular waves. In particular the aspects concerning higher harmonics and their trends with respect to speed, wave and hull geometrical characteristics.